Amphiphilic polymer-mediated formation of laponite-based nanohybrids with robust stability and pH sensitivity for anticancer drug delivery - Wang, Guoying (2019)
The development of pH-sensitive drug delivery nanosystems that present a low drug release at the physiological pH and are able to increase the extent of the release at a lower pH value (like those existent in the interstitial space of solid tumors (pH 6.5) and in the intracellular endolysosomal compartments (pH 5.0)) is very important for an efficient and safe cancer therapy. Laponite (LP) is a synthetic silicate nanoparticle with a nanodisk structure (25 nm in diameter and 0.92 nm in thickness) and negative-charged surface, which can be used for the encapsulation of doxorubicin (DOX, a cationic drug) through electrostatic interactions and exhibit good pH sensitivity in drug delivery. However, the colloidal instability of LP still limits its potential clinical applications. In this study, we demonstrate an elegant strategy to develop stable Laponite-based nanohybrids through the functionalization of its surface with an amphiphile PEG-PLA copolymer by a self-assembly process. The hydrophobic block of PEG-PLA acts as an anchor that binds to the surface of drug-loaded LP nanodisks, maintaining the core structure, whereas the hydrophilic PEG part serves as a protective stealth shell that improves the whole stability of the nanohybrids under physiological conditions. The resulting nanocarriers can effectively load the DOX drug (the encapsulation efficiency is 85%), and display a pH-enhanced drug release behavior in a sustained way. In vitro biological evaluation indicated that the DOX-loaded nanocarriers can be effectively internalized by CAL-72 cells (an osteosarcoma cell line), and exhibit a remarkable higher anticancer cytotoxicity than free DOX. The merits of Laponite/PEG-PLA nanohybrids, such as good cytocompatibility, excellent physiological stability, sustained pH-responsive release properties, and improved anticancer activity, make them a promising platform for the delivery of other therapeutic agents beyond DOX.